“Love is...”: An Inaesthetic Inquiry on Love and Attention in Aureus Solito’s The Blossoming of Maximo Oliveros - De Chavez, Jeremy (Archīum Ateneo, 2024)
Drawing from Alain Badiou’s concept of inaesthetics, which proposes that art conditions philosophical thought, this essay offers an inaesthetic reading of The Blossoming of Maximo Oliveros (2005) and suggests that it is a film that offers enabling possibilities in the thinking of love by providing the spectator with a different experience of cinematic attention in the visual field. The author suggests that the film raises the philosophical question “What is love?” and attempts to answer the very question it poses through punctual encounters, which are moments of cinematic interruption—described by Roland Barthes as “what I add . . . and what nonetheless is already there” (A Lover’s Discourse 55)—that may offer opportunities for philosophical speculation. This essay further argues that those punctual moments initiate a new form of attention that is not sustained by “visual pleasure,” as theorized by Laura Mulvey, but by the “movement of thought” (Badiou, Cinema 17). The film uses that mode of attention as a way to think about love while also suggesting that love itself is a form of attention.